MANAJEMEN KURIKULUM BERBASIS DIGITAL DI PONDOK PESANTREN AL RIYADL CIPANAS - Rubiherlan, Yusuf; Juningsih, Juningsih; Nursanti, Funny Eka; Soleh, Wiwi Sulastri; Rostini, Deti; Wasliman, Eva Dianawati (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: Al-Riyadl Islamic Boarding School is a pure Salafi Islamic boarding school, which only holds yellow book recitations using the sorogan, balagan and wetonan methods. In carrying out its learning, continuing to keep up with the times, Al-Riyadl Islamic Boarding School does not abandon the old tradition, namely pure Salafi. Al-Riyadl Islamic Boarding School responds to technological developments in relation to digital-based curriculum management. The case study in this research was used to determine the planning, organizing, commanding, coordinating and supervising of the Al-Riyadl Islamic Boarding School in response to technological developments in relation to digital-based curriculum management. Qualitative methodology is used in research that focuses on natural conditions in a place or event and uses stages in accordance with the rules or steps required for data collection. Al-Riyadl Islamic Boarding School is located in a community environment that does not have closed borders or fortifications like Islamic boarding schools in general. Combining formal and non-formal education with the aim of maximizing the organization and supervision of students while not eliminating the old tradition of Islamic boarding schools. The digital-based Islamic boarding school curriculum includes several subjects such as inheritance and astronomy lessons using scientific calculators. The use of smartphones and laptops is also carried out during evaluations where the test questions are done digitally and also includes elements of technology in Islamic boarding school management, although not yet optimally, but for the next school year we will make more mature plans in implementing digitalization.Keyword : Boarding School, Curriculum, DigitalizationAbstrak: Pesantren Al-Riyadl merupakan Pesantren Salafi murni, yang  hanya mengadakan pengajian kitab kuning dengan metode sorogan, balagan, dan wetonan. Dalam melaksanakan pembelajarannya, terus mengikuti perkembangan zaman, Pesantren Al-Riyadl tidak meninggalkan tradisi lama yakni salafi murni. Pesantren Al-Riyadl menyikapi perkembangan teknologi dalam hubungannya dengan manajemen kurikulum berbasis digital. Studi kasus dalam penelitian ini digunakan  untuk mengetahui perencanaan, pengorganisasian, pengkomandoan, pengkoordinasian, dan pengawasan Pesantren Al-Riyadl menyikapi perkembangan teknologi dalam hubungannya dengan manajemen kurikulum berbasis digital. Metodelogi kualitatif digunakan dalam penelitian yang mengarah pada kondisi alamiah di suatu tempat atau kejadian dan menggunakan tahapan-tahapan sesuai dengan aturan atau langkah yang diperlukan untuk pengumpulan data. Pesantren Al-Riyadl berlokasi di lingkungan masyarakat yang tidak memiliki batas atau benteng tertutup seperti pada pesantren pada umumnya. Penggabungan pendidikan formal dan nonformal dengan tujuan agar pengorganisasian dan pengawasan kepada para santri lebih maksimal dengan tetap tidak menghilangkan tradisi lama sebagai pondok pesantren. Kurikulum pesantren berbasis digital dimasukan pada  beberapa mata pelajaran seperti pelajaran waris dan falak dengan media kalkulator saintifik. Penggunaan smartphone dan laptop juga dilakukan saat evaluasi dimana soal tes dikerjakan secara digital juga memasukan unsur  teknologi dalam manajemen pesantren, meskipun belum secara maksimal, tetapi untuk tahun ajaran kedepannya akan membuat perencanaan yang lebih matang dalam penerapan digitalisasi. Kata Kunci : Kurikulum, Digital, Pesantren